The efficacy and tolerability of scalp cooling in preventing chemotherapy-induced alopecia in patients with breast cancer receiving anthracycline and taxane-based chemotherapy in an Asian setting - Saad, Marniza; Chong, Flora Li Tze; Bustam, Anita Zarina; Ho, Gwo Fuang; Malik, Rozita Abdul; Ishak, Wan Zamaniah Wan; Phua, Vincent Chee Ee; Yusof, Mastura Md; Yap, Ning Yi; Alip, Adlinda (Medknow Publications, 2018)
BACKGROUND: Scalp cooling has been shown in several studies to be an effective method in preventing chemotherapy-induced alopecia (CIA). Data on the use of scalp cooling in Asian countries are limited, and evidence for its use and efficacy among our patients are not available. OBJECTIVE: The aim of this study was to assess the effectiveness and tolerability of scalp cooling among breast cancer patients in our study population. METHODS: Consecutive breast cancer patients receiving FE 75 C, FE 100 C, FE 100 C-D, docetaxel 75 or docetaxel, and cyclophosphamide (TC) at our treatment center were recruited and allocated to the treatment (scalp cooling, DigniCapTM system) or control group in this prospective nonrandomized controlled study. The assessment of alopecia was carried out using the World Health Organization grading system and clinical photographs. RESULTS: Seventy patients were recruited, but only 25 completed the study and were evaluable for analysis. Five of 12 patients (42%) in the scalp cooling group managed to preserve hair. Two of three patients who received FE 75 C and TC regimens had minimal hair loss. All patients treated with FE 100 C had severe hair loss. Half of all patients who received scalp cooling throughout chemotherapy rated the treatment as reasonably well tolerated. The most common reason for discontinuing scalp cooling was intolerance to its side effects. CONCLUSION: Scalp cooling is potentially effective in reducing CIA caused by docetaxel, TC, and FE 75 C chemotherapy regimen. However, it was not well tolerated by our study population. The dropout rate was high, and this needs to be taken into consideration when pursuing further trials in a similar setting.